Comparative Morphological Characteristics of Primary Cultures of Neonatal Animal Adrenal Cells - Novikova, Olga Yu.; Plaksina, Ekaterina M.; Sidorenko, Olga S.; Lavrik, Aleksey A.; Bozhok, Galina A.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):178.